The Impact of Career Growth on Knowledge-Based Employee Engagement: The Mediating Role of Affective Commitment and the Moderating Role of Perceived Organizational Support - Jia-jun, Zhu; Hua-ming, Song (Frontiers in Psychology, 2022)
Based on social exchange theory and attribution theory, this paper explores the role of affective commitment and organizational support in the relationship between career growth and engagement of knowledge workers. The results show that: (1) Career growth has a positive impact on knowledge workers’ organizational engagement. Career goal progress and career ability development in career growth promote job engagement. (2) Career growth has a positive effect on affective commitment, which in turn influences on employee engagement. (3) Affective commitment plays a mediating role in the effect of career growth on engagement. (4) Perceived organizational support positively moderates the relationship between career growth and affective commitment.